2019
DOI: 10.1111/jbi.13672
|View full text |Cite
|
Sign up to set email alerts
|

Environmental latitudinal gradients and host‐specificity shape Symbiodiniaceae distribution in Red Sea Porites corals

Abstract: Aim The aim of the study was to assess the diversity of algal symbionts of the family Symbiodiniaceae associated with the coral genus Porites in the Red Sea, and to test for host‐specificity and environmental variables driving biogeographical patterns of algal symbiont distribution. Location Saudi Arabian Red Sea. Taxon Endosymbiotic dinoflagellates of the family Symbiodiniaceae in association with the reef‐building coral genus Porites. Methods Eighty Porites coral specimens were collected along the Saudi Arab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 85 publications
7
47
0
Order By: Relevance
“…As delineations of coral-Symbiodiniaceae associations continue to be conducted at more fine-scale resolutions, high-fidelity associations as seen here continue to be resolved (Smith et al 2017;Lewis et al 2019;Terraneo et al 2019). Such characterizations evidence a considerable pool of phenotypically distinct associations upon which mechanisms of adaptation may act and build upon the considerable evidence pointing toward a prevalence of host specificity within the Symbiodiniaceae (Santos et al 2004;Smith et al 2017;Thornhill et al 2017).…”
Section: Further Characterization Of Coral Host-specific Symbiodiniacmentioning
confidence: 74%
See 1 more Smart Citation
“…As delineations of coral-Symbiodiniaceae associations continue to be conducted at more fine-scale resolutions, high-fidelity associations as seen here continue to be resolved (Smith et al 2017;Lewis et al 2019;Terraneo et al 2019). Such characterizations evidence a considerable pool of phenotypically distinct associations upon which mechanisms of adaptation may act and build upon the considerable evidence pointing toward a prevalence of host specificity within the Symbiodiniaceae (Santos et al 2004;Smith et al 2017;Thornhill et al 2017).…”
Section: Further Characterization Of Coral Host-specific Symbiodiniacmentioning
confidence: 74%
“…Our use of the SymPortal pipeline in conjunction with relatively deep NGS amplicon sequencing has enabled fine-scale resolutions of Symbiodiniaceae communities and genotypes in the Thuwal reef system. Resources to which these resolutions may be directly compared are limited (but see Gardner et al 2019;Terraneo et al 2019;Camp et al 2020) given the only recent availability of such analytical approaches (approaches able to appropriately handle Symbiodiniaceae intragenomic ITS2 variability), but some genotypes may be related to previous resolutions if ITS2 intragenomic characteristics have been utilized. For example, the definitions of C. thermophilum or multiple Durusdinium species all include ITS2 intragenomic characterizations (LaJeunesse et al 2014;Hume et al 2015).…”
Section: Further Characterization Of Coral Host-specific Symbiodiniacmentioning
confidence: 99%
“…For the last decade, high-throughput sequencing has been a mainstream technique for characterizing coral endosymbionts [ 9 , 75 , 107 , 108 ]. Most recently, development of the SymPortal analytical framework specifically for the processing of ITS2 amplicon data obtained from HTS has allowed us to characterize Symbiodiniaceae communities at a much finer resolution by accounting for intragenomic ITS2 diversity [ 81 , 109 , 110 ]. Overall, we found qPCR and HTS to produce consistent patterns of relative Durusdinium and Cladocopium abundances ( Figure 2 ), even though the relationship between relative qPCR-estimated concentrations and HTS read abundances was weak ( Figure S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Species identification of each colony was confirmed via a combination of in situ colony and corallite photographs, as well as observations of the ventral triplet septal arrangement performed under a stereo microscope according to Veron 51 and Forsman et al 52 . Analyses indicated that all collected specimens were of one species putatively identified as Porites lutea 53,54 .…”
Section: Methods Field Sampling Bacterial Sample Collectionmentioning
confidence: 99%